Pica in childhood: Prevalence and developmental comorbidity - Lesinskienė, Sigita; Stonkutė, Greta; Šambaras, Rokas (Frontiers in Child and Adolescent Psychiatry, 2023)
Background Pica is an eating disorder in which a person feels the urge to eat non-nutritious, non-food substances. It can occur at any age; however, a higher prevalence is observed among children with mental health issues and pregnant women. Recently, additional attention has been given to the role of sensory sensitivity in eating disorders. Aim of the study To examine the prevalence of pica in preschool children and explore the associations with increased sensory sensitivity traits and rates of internalizing and externalizing difficulties. Methodology Parents/guardians of children aged 3–6 years were asked to complete an anonymous online questionnaire containing demographic data, questions regarding the peculiarities of children's eating, sensory sensitivity. Furthermore, a Strengths and Difficulties Questionnaire was also completed. This study included 655 participants. Of those 655, 41 study participants who did not complete the questionnaire were excluded. The final sample consisted of 614 participants who had completed the questionnaire. Results Approximately, 3.7% of participants indicated that their child ate non-nutritious, non-food substances. Children with increased sensory sensitivity traits in response to sounds (p = 0.008), visual stimuli (p < 0.001), and skin contact (p = 0.006) ate significantly more non-nutritious non-food substances. Those who had higher scores on internalizing and externalizing difficulties had more difficulties associated with eating. Children who had increased sensory sensitivity to sounds, visual stimuli, or skin contact had significantly more internalizing difficulties (p < 0.05). There were no significant differences between higher externalizing difficulties and increased sensory sensitivity to sounds, visual stimuli, skin contact, or smells (p > 0.05). Conclusions Children with increased sensory sensitivity traits were more likely to eat inedible substances than those without. Furthermore, children who had increased sensory sensitivity traits were significantly more picky about food and had more internalizing difficulties. It is important for specialists to combine clinical data on the characteristics of a child's development, including sensory, eating, and emotional health aspects.